Animateur.rice dans l’école. Un métier travaillé par la forme scolaire - Simon Kechichian (La Nouvelle Revue du Travail, 2022)
Based on an ethnographic survey of after-school leisure facilities in working-class neighborhoods, the article sheds light on how a school and its form affect the work that staff performs under these conditions. It shows that scholastic domination has various ways of affecting staff’s working times and conditions; ways of being and doing; and ways of understanding and producing leisure activities. Contrary to a professional discourse that depicts this universe as a non-scholastic space, the article will show that after-school professionals are prisoners of a school’s form and help to extend socialisation’s scholastic mode to encompass a school’s peripheral boundaries.